2012
DOI: 10.1590/s0034-89102012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Incidência da sífilis congênita no Brasil e sua relação com a Estratégia Saúde da Família

Abstract: OBJECTIVE: To estimate the incidence of congenital syphilis and identify its relationship with Family Health Strategy coverage. METHODS:An observational ecological study was carried out with both descriptive and analytical components, by two different approaches: one that explores a temporal series (2003 to 2008) RESULTS:Increasingly trends of congenital syphilis notifi cation in Brazil refl ect social inequalities in the distribution of cases. The incidence of congenital syphilis was lower in the municipal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
83

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 20 publications
3
36
1
83
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18]19 In this regard, it was found that the majority of pregnant women (55%) studied did only oneVDRL test, indicating non-compliance with the Protocol of attention to prenatal care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16][17][18]19 In this regard, it was found that the majority of pregnant women (55%) studied did only oneVDRL test, indicating non-compliance with the Protocol of attention to prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…5,19 It is imperative to strengthen the primary care, so that the syphilis is diagnosed and treated early, yet in prenatal period, preventing the occurrence of congenital syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…11 Outro estudo, desenvolvido na cidade de Campo Grande, capital do Mato Grosso do Sul, demonstrou que 91,3% das gestantes infectadas também residiam em área urbana.…”
Section: Introductionunclassified
“…Quando analisado o total de parceiros que souberam do diagnóstico de sífilis na gestante antes ou durante o pré-natal, apenas seis (24%) parceiros realizaram o tratamento adequado 2 . Assim, percebe-se que a maioria dos parceiros não são tratados, o que parece ser um problema vivenciado em diferentes regiões do país 8,11,13,21 .…”
Section: Discussionunclassified
“…Pode também estar associada à visão que os homens têm em relação à saúde, pois atribuem à mulher a responsabilidade pelo cuidado 23,24 . Por outro lado, existem ainda questões inerentes aos serviços 21,25 e ao comportamento dos parceiros, como é o caso do uso de drogas e álcool 26 .…”
Section: Discussionunclassified